Preparation and in- vitro Evaluation of Bioadhesive Vaginal Film of Tinidazole - Thomas, Lena Murad; Al-Akkam, Entidhar J.; Daood, Noor Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2024)
Bioadhesive vaginal film is becoming a more effective and convenient dosage form compared to suppositories and gel for vaginal application as a method for the treatment of vaginal infections. This study aimed to prepare and characterize bioadhesive films of tinidazole to be used for vaginal delivery over a prolonged period to treat local infections.Fourteen formulas of tinidazole films were prepared by solvent evaporation method. Each film was composed of 10 mg tinidazole with different ratios and concentrations of a polymeric combination of polyvinyl alcohol/ polyvinyl pyrrolidone (PVA/PVP) or polyvinyl alcohol/ hydroxypropyl methylcellulose (PVA/HPMC) for formulas A1-A7 and B1-B7, respectively. The prepared films were evaluated for their physicochemical characteristics, content uniformity, swelling, mucoadhesive strength, mucoadhesive time, and drug release. All the prepared films were transparent, had a uniform thickness (0.1-0.15 mm), and exhibited sufficient flexibility with drug content uniformity. The mucoadhesive strength of films was in the range of 28 ± 0.2 to 75 ± 0.01 g. Films containing PVA/HPMC showed higher swelling and lower mucoadhesive strength than those containing PVA/PVP polymeric combination. The in vitro drug release study showed no significant differences (p > 0.05) among films containing PVA/PVP or PVA/HPMC polymeric combinations.Formulas A3 and B4 were considered as the optimal bioadhesive films containing 3% of PVA: PVP (4:1) and 4% of PVA: HPMC (2:1), respectively as they showed complete flexibility, acceptable mucoadhesive strength and time (43 ± 0.1, 45 ± 0.23 g and 30 ± 0.02, 34 ± 0.01 min, respectively) and prolonged drug release rate. In conclusion, films of formulas A3 and B4 possess the potential as a delivery system for tinidazole for the treatment of vaginal infections at the site of application.